Students’ Problems for not Completing English Homework - Fitri, Mainar; Andriani, Weli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The purpose of this research was to describe students’ dominant reason for not completing their English homework. This research was descriptive quantitative research. The population of this research were students of a senior high school in Indonesia. In this research, the researchers took the sample by using purposive sampling technique. So, the total of sample of this research were 59 students from the total number of the population. The instrument used in this research was a questionnaire. The researchers gave 8 items of statements which consisted of four indicators (behaviorism theory, constructivism theory, maturational theory, and ecological system theory). Based on the result of the research, it was found that the students’ dominant reason for not completing English homework was maturational theory with the percentage was 29% with the mean 3.83 categorized into high level. The researcher concludes that the most dominant reason the students do not do the homework because the students are not developmentally ready to complete the task and do not understand the homework (maturational theory).